Influence of incalculation parameter to shock-wave structures in supersonic channel with jet injection (Journal of Mathematics Mechanics and Computer Science, 2015)
Turbulent stream of air with perpendicular injection of round sonic hydrogen jet from the chink placed on the bottom wall is numerically modeling in flat channel. Solution of governing averaged by Favre Navier-Stokes equations for ideal multi component gas was made by WENO scheme. For closure aims k-? model of turbulence was chosen. For initial conditions parameters of stream were taken. For boundary conditions: slip conditions for bottom and top wall; stream conditionsfor entrance boundary; not reflection condition for outlet boundary and jet parameters on the jet injection were fixed. At the initial moment thickness of boundary layer with given profiles of velocity, temperature, pressure and density are given. Distribution of pressure on the bottomwall in the region of slot is compared with the experimental data. Besides of it plots for isobars, taken with ENO and WENO schemes, are qualitatively compared with the works of other authors. Influence of incalculation parameter to the shock-wave structures, formed from the interaction of bow shock wave with the boundary layers of bottom and top walls. It was found, that the incidence of bow shock is enlarged with the increasing of incalculation parameter.
Keywords: supersonic flow; ideal gas; Naver-Stokes eqations; shock wave; boundary layer